The surgical techniques of transperineal anastomotic urethroplasty for complex posterior urethral stenosis in boys and the long-term follow up outcomes - Zhu, Weidong; Song, Lujie; Sa, Yinglong; Xu, Yuemin; Fu, Qiang (Frontiers in Pediatrics, 2023)
Objective: To explored the curative effects of various surgical methods used to treat complicated posterior urethral strictures in boys and the long-term complication. Methods: We retrospectively studied 28 boys under 14 years of age with complicated posterior urethral strictures treated at our hospital from January 2015 to December 2020. Urethral angiography revealed posterior urethral strictures. Twelve had previously failed urethral surgery; four had urethral fistulae. All underwent end-to-end urethral anastomoses via a transperineal, inferior pubic approach. We freed the distal end of the urethra, split the penile cavernous septum, partially resected the lower edge of the pubic symphysis, and rerouted the urethra under a corpus cavernosum to reduce the tension of the urethral anastomosis. Results: All boys were 2–14 years of age at the time of surgery (mean 6.3 years). The urethral strictures were 3–5.5 cm in length (mean 4.2 cm). Catheters were removed 4 weeks postoperatively. The postoperative follow-up time was 4–72 months (mean 36.8 months). Twenty-four patients exhibited unobstructed urination after a single operation. The maximum urinary flow rate was 15–22 mL/s (average 17.8 mL/s); the success rate was 85.7%. Two patients required second urethral end-to-end anastomoses; urination became normal postoperatively. Two continued to exhibit cystostomies, and two evidenced mild incontinence. Of the six children who have attained puberty, two report erectile dysfunction. Conclusion: End-to-end urethral anastomosis via a transperineal inferior pubic approach is an ideal treatment for posterior urethral strictures in boys. The complications include incontinence and erectile dysfunction, and require long-term follow-up.